Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I have a couple of questions where I use the MVT and I wanted your opinion on the appropriateness of my proofs.

Let $F()$ be a function such that $\lim_{x\to\infty} F'(x)=0 $ and let $G(x,y)$ be a function such that $\lim_{x\to\infty} G(x,y)=\infty $ and $G(x,y_1) > G(x,y_2)$ for all $x, y_1>y_2$. Assume that $F(0)=0$ and that $F$ and $G$ are both always non-negative.

Question: Given a>b, Does $\lim_{x->\infty} F(G(x,a)-F(G(x,b))=0 $?

My Answer: Yes, since by the MVT: $F(G(x,a)-F(G(x,b))=F'(g)[G(x,a)-G(x,b)]$

As $x\to\infty, g\to\infty,$ and thus, $F'(g)\to0$ But, I still have $(G(x,a)-G(x,b))$ and I have to show this is bounded?

Similarly, I have the following question.

Let G be the function as described above and and now assume that $\lim_{x\to\infty} F'(x)=\infty $, would it now follow (by similar reasoning) that $\lim_{x\to\infty} F(G(x,a)-F(G(x,b))=\infty $?

share|cite|improve this question
LaTeX hint: use \to for arrows, like x \to \infty – Ilya Jan 10 '13 at 17:12
Thanks, edited. – Greg Jan 10 '13 at 19:50
up vote 1 down vote accepted

Yes, you would need an extra assumption to guarantee the boundedness of that difference. Otherwise a counterexample would be given by $F(x) = \sqrt{x}$, $G(x,0) = x^2,\, G(x,1) = 2x^2$.

A similar counterexample can be given for your second question.

share|cite|improve this answer
Thanks, I've posted a related follow up question in case youre interested – Greg Jan 11 '13 at 17:23

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.